A study on antioxidant activities of palm puree extracts / Mawardi Hassan - Hassan, Mawardi (Faculty of Applied Sciences, 2009)
This study was conducted on palm puree that derived from oil palm fruit to investigate their antioxidant activities. The extracts of palm puree using two types of solvents such as water and ethanol were analysed for total phenolic content, ferric reducing antioxidant power (FRAP), and DPPH (1, 1-Diphenyl- 2- picrylhydrazyl ) free radical scavenging activities. The ethanolic extract of palm puree showed the highest total phenolic content, reductive potential, and high percent in free radical scavenging as compared to the aqueous extract. Increasing the concentration of the extracts resulted in increased Fe3+ reducing antioxidant power for both of the extracts but the reductive potential of BHA/BHT ( a synthetic antioxidant) was significantly higher than that of both of the palm puree extracts and vitamin C at all concentrations. In DPPH radical scavenging analysis, both of the palm extracts showed a dose-dependent antioxidant activity. The percent scavenging of BHA/BHT and vitamin C were remarkably higher than that of palm extracts at all concentrations. This shows the palm puree extracts showed weak reductive potential and radical scavenging as compared to BHA/BHT which gave a very strong reductive potential and also radical scavenging.